Review of Previous & Current Fisheries Agreements concluded by some African Union Member states in West & Central Africa - Failler, Pierre (AU-IBAR, 2015)
Numerous fisheries agreements result in the significant loss of benefits for African countries due to their flawed formulation as a result of weak negotiating capacities. The relatively low involvement of fishing communities in the negotiation process contributes to the development of such agreements.
Keywords: FishGov1 Project